IDENTIFIKASI SKEMA WARNA PADA COLOR GRADING SEBAGAI PEMBANGUN MOOD DALAM FILM ANIMASI PIXAR “COCO” - Savina Rachma Oktaviandry; Virginia Suryani Setiadi (Jurnal Dimensi DKV Seni Rupa dan Desain, 2023)
Movie “Coco”. Color grading is one of the important factors in the cinematography of a film. The atmosphere in a film can be formed with different coloring for each scene so that it can build the right atmosphere. This research was conducted to identify the color scheme in color grading as a mood builder in Pixar’s animated film “Coco”, using a qualitative approach, and descriptive method. Data collection comes from various visual sources and library references. From this research, it is concluded that the color scheme in color grading in Pixar’s animated film “Coco” successfully builds the audience’s mood by using different color schemes for each scene. The color schemes that are often used in the animated film are derivatives of orange, blue, and purple. The results of research journals on color grading as a mood builder in Pixar’s animated film “Coco” are expected to be one of the reference sources or references, especially textual studies on color grading. This research journal is also expected to contribute as a reference development study in multimedia, using an approach regarding color schemes as mood builders in a film. Keywords: color grading, color scheme, mood, animation, Coco